2019
DOI: 10.3390/en13010152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combustion Models for Lifted Hydrogen Flames within RANS Framework

Abstract: Within the framework of a Reynolds averaged numerical simulation (RANS) methodology for modeling turbulence, a comparative numerical study of turbulent lifted H 2 /N 2 flames is presented. Three different turbulent combustion models, namely, the eddy dissipation model (EDM), the eddy dissipation concept (EDC), and the composition probability density function (PDF) transport model, are considered in the analysis. A wide range of global and detailed combustion reaction mechanisms are investigated. As turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Hence, simulations of combustion of a complex fuel under gas turbine conditions are very demanding and time consuming, even on a super-computer. An attractive alternative that requires significantly less computational power is to solve the Reynolds Averaged Navier-Stokes (RANS) equations combined with a suitable combustion model (Benim and Pfeiffelmann 2019). This method does not resolve all the fine details that a LES simulation does, neither is it capable of predicting all of the phenomena that a LES simulation can capture, e.g.…”
Section: Tablementioning
confidence: 99%
“…Hence, simulations of combustion of a complex fuel under gas turbine conditions are very demanding and time consuming, even on a super-computer. An attractive alternative that requires significantly less computational power is to solve the Reynolds Averaged Navier-Stokes (RANS) equations combined with a suitable combustion model (Benim and Pfeiffelmann 2019). This method does not resolve all the fine details that a LES simulation does, neither is it capable of predicting all of the phenomena that a LES simulation can capture, e.g.…”
Section: Tablementioning
confidence: 99%
“…In the paper, the turbulent flows were described with account of recommendations in [26][27][28], and the standard k-ε model [29][30][31] turbulence model was used.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, experimental data from Sautet et al [15] and Wu et al [16] were taken as a basis for non-reacting and reacting flows respectively. Benim et al [17] referred to the same experimental setups within their 2D study, a schematic drawing of which is shown in Fig. 1.…”
Section: Experimental Reference Casesmentioning
confidence: 99%
“…Although not optimized for hydrogen chemistry, GRI-Mech 3.0 can be considered partially validated for the stoichiometric combustion of hydrogen and air. Further increasing the variety of mechanisms covered by the recent 2D simulations from Benim et al [17], besides GRI-Mech 3.0 the mechanism by Jachimowski [22] was included in the present study. It features a comparably broad temperature range as for Li and Ó Conaire, whereas equivalence ratio and pressure are more limited.…”
Section: Chemical Reaction Mechanismsmentioning
confidence: 99%